Desain Dan Pembangunan Aplikasi Penjualan Buku Berbasis Website Di Toko Buku Murah Medan - Latifah, Laili; Yusup, Mohammad; Supiyandi (Universitas Sari Mutiara Indonesia Medan, 2024)
Modern technology has developed rapidly, providing various solutions to facilitate activities and work. Toko Buku Murah Medan, which focuses on book sales, still uses manual methods in managing its sales. This manual process often causes various problems, such as data input errors and delays in making reports. To overcome these problems, this study aims to design and build a website-based book sales information system application. This study uses data collection methods through observation, interviews, and documentation. In developing the application, the Personal Home Page (PHP) method is applied because of its flexibility in handling changing needs during the development process. Direct communication with clients is the main focus in this method. This application is developed using Visual Studio Code as an editor, and MySQL as a database, thus accelerating the application development process. The results of this study are in the form of a website-based book sales information system application that is able to manage sales data, purchases, and book stock more efficiently. This system also provides an automatic report generation feature, both daily, weekly, and monthly, which can improve performance and efficiency at Toko Buku Murah Medan. With this application, problems arising from manual processes can be minimized, supporting improved service and store operations.